Perkembangan dan Tantangan Islam Negeri Barat: Studi Tokoh Dakwah Imam Shamsi Ali Di Kota New York Amerika Serikat - Amjad Trifita (Jurnal Al-Hikmah: Jurnal Dakwah, 2022)
The development of Islamic history will not be separated from a number of people who have a dominant role and great influence. These are the people who later become the central figures, and charismatic leaders whose traces of character have colored the history of human life. This study aims to examine a figure who has an influence on the development of Islamic da'wah in the United States. This paper uses a character study approach, so that it can be known and understood how it is applied in the pursuit of Islamic da'wah in America. The basic concept of character studies used in this research is the object of character study which includes his empirical biography, thoughts, roles and social contributions in various fields. The character study method was applied to examine the da'wah figure Imam Shamsi Ali in terms of his da'wah gait, popularity, influence and intellectual work while preaching in New York City, United States. The results of this study indicate that Shamsi Ali's da'wa gait in New York had a considerable influence on the development of Islamic da'wah in America, until he was named one of the seven most influential religious figures in New York City. His da'wah contributions include becoming a mosque imam, establishing the Nusantara Foundation, establishing the first Islamic boarding school in America, and being a pioneer of the telling Islam to the world movement.